Effectiveness of Different Benfotiamine Dosage Regimens in the Treatment of Painful Diabetic Neuropathy - Winkler, Gabor; Pál, Borbála; Nagybégányi, Emese; Öry, Ivan; Porochnavec, Marietta; Kempler, Peter (Arzneimittelforschung, 1999)
The therapeutic effectiveness of a benfotiamine (CAS 22457-89-2)-vitamin B combination (Milgamma-N®), administered in high (4 × 2 capsules/day, = 320 mg benfotiamine/day) and medium doses (3 × 1 capsules/day), was compared to a monotherapy with benfotiamine (Benfogamma®) (3 × 1 tablets/day, = 150 mg benfotiamine/day) in diabetic patients suffering from painful peripheral diabetic neuropathy (DNP). In a 6-week open clinical trial, 36 patients (aged 40 to 70 yrs) having acceptable metabolic control (HbA1c, < 8.0%) were randomly assigned to three groups, each of them comprising 12 participants. Neuropathy was assessed by five parameters: the pain sensation (evaluated by a modified analogue visual scale), the vibration sensation (measured with a tuning fork using the Riedel-Seyfert method) and the current perception threshold (CPT) on the peroneal nerve at 3 frequencies: 5, 250 and 2000 Hz). Parameters were registered at the beginning of the study and at the end of the 3rd and 6th week of therapy. An overall beneficial therapeutic effect on the neuropathy status was observed in all three groups during the study, and a significant improvement in most of the parameters studied appeared already at the 3rd week of therapy (p < 0.01). The greatest change occurred in the group of patients receiving the high dose of benfotiamine (p < 0.01 and 0.05, resp., compared to the other groups). Metabolic control did not change over the study. It is concluded that benfotiamine is most effective in large doses, although even in smaller daily dosages, either in combination or in monotherapy, it is effective.
Keywords: Benfogamma ®; Benfotiamine, combination with vitamin B, effectiveness in diabetic neuropathy; CAS 22457-89-2; Milgamma-N ® 1 Peripheral diabetic neuropathy